CONCEPTUAL FRAMEWORKS FOR SHAPING AND ADVANCING AGROTOURISM VENTURES - Sadafbek Husanboev (American Journals, 2023)
This study delves into the foundational underpinnings driving the inception and growth of agrotourism endeavours. Exploring theoretical frameworks and conceptual models, it investigates the fundamental principles shaping the evolution and sustenance of agrotourism activities. By examining theoretical bases, this research illuminates the conceptual landscape underpinning the formation and dynamic progression of agrotourism ventures. It navigates through diverse theoretical perspectives, elucidating the core principles that drive the development and evolution of agrotourism within socio-economic contexts. This exploration seeks to provide a comprehensive understanding of the theoretical foundations instrumental in shaping and propelling the growth of agrotourism initiatives, contributing to the strategic development and management of these ventures.
Keywords: Agrotourism, Theoretical Frameworks, Tourism, Agriculture, Conceptual Models, Socio-economic Contexts, Sustainability, Rural Development.